“You Can’t Play a Sad Song on the Banjo:” Acoustic Factors in the Judgment of Instrument Capacity to Convey Sadness - David Huron; Neesha Anderson; Daniel Shanahan (Empirical Musicology Review, 2014)
Forty-four Western-enculturated musicians completed two studies. The first group was asked to judge the relative sadness of forty-four familiar Western instruments. An independent group was asked to assess a number of acoustical properties for those same instruments. Using the estimated acoustical properties as predictor variables in a multiple regression analysis, a significant correlation was found between those properties known to contribute to sad prosody in speech and the judged sadness of the instruments. The best predictor variable was the ability of the instrument to make small pitch movements. Other variables investigated included the darkness of the timbre, the ability to play low pitches, the ability to play quietly, and the capacity of the instrument to "mumble." Four of the acoustical factors were found to exhibit a considerable amount of shared variance, suggesting that they may originate in a common underlying factor. It is suggested that the shared proximal cause of these acoustical features may be low physical energy.